Income, wealth and economic inequality in Australia. Issue 4 (19th August 2018) - Tapper, Alan; Fenna, Alan
Abstract: Economic well‐being and economic inequality are usually quantified using income measurements of various sorts. Such analyses overlook the contribution of wealth – a potentially very significant factor. In this article, we integrate wealth and income data to provide a more comprehensive accounting of economic well‐being and economic inequality in Australia. Using the Australian Bureau of Statistics Household Expenditure Survey microdata for 2009–2010, we present a cross‐sectional analysis of wealth‐adjusted income. We examine the relative contributions of income and wealth to wealth‐adjusted income and compare the distribution of wealth‐adjusted income to the distribution of income and the distribution of wealth. Wealth, we find, makes up between one‐fifth and two‐fifths of wealth‐adjusted income; the incorporation of wealth increases the inequality already present in the income distribution (as measured using final incomes) by about 25 per cent.